Increasing Creativity on Early Childhood Education Teachers through Educational Toys - Pusari, Ratna Wahyu; DH, Dwi Prasetiyawati (Universitas Negeri Semarang, 2014)
Research on â€œIncreasing Creativity On Early Childhood Education Teachers Through Educational Toysâ€ aims to know the pedagogical competencies on the teachers of Early Childhood Education (ECE) in Ungaran; determine the level of creativity on ECE teachers; and know what the efforts is being done by ECE teachers to improve their pedagogic competence. The research procedure uses descriptive data in the form of words derived from a variety of data collection techniques used in this research is by using the method of observation, questionnaires and interviews. This research was conducted in four phases: Phase I: Preface/initial field observations carried out with; Phase II: Initial development, design to identify the level of creativity of ECE teachers in Ungaran; Phase III: Conducting interviews, filling the questionnaire about creativity in educational toys; and Phase IV: analyzing the creativity level of ECE teachers. The conclusions of this study are 1.The level of creativity ECE teachers in Ungaran is low; 2. The low of creativity in ECE teachers in Ungaran is due to (a) low of innovations Â in learning; (b) teachers is not able to use the materials around as an aid to learning; (c) the assumption of the teachers that the success of learning is determined by using expensive and luxurious media; (d) openness to new information in the world of education, particularly in ECE; and 4. According to the motto of learning in early childhood â€œLearning while Playingâ€ the media which is used for Educational Games is made from used/recycled materials.How to citePusari, R., & DH, D. (2014). Increasing Creativity on Early Childhood Education Teachers through Educational Toys. Indonesian Journal Of Early Childhood Education Studies, 3(2), 108-113. doi:10.15294/ijeces.v3i2.9483